Evaluation of veracity of car braking parameters used for the analysis of road accidents - Nagurnas, Saulius; Mitunevičius, Valentinas; Unarski, Jan; Wach, Wojciech (Transport, 2007)
During the road accident analysis speed of the examined vehicle often is being established in accordance with the length of the trace remained by the vehicle tires. Usually in such case there are values of braking deceleration used for calculations, which are selected from the corresponding references. The real experiment, establishing the braking parameters of the given vehicle, is performed more seldom. In both cases it is important to calculate the vehicle speed in accordance with the received or found values of deceleration as well to estimate the possible limits of the vehicle speed, i.e. to evaluate the veracity of such calculations. This paper presents the results of evaluation of car braking parameters, which are treated as random values in the known probabilistic characteristics.First Published Online: 27 Oct 2010